Comparative omics analyses of hepatotoxicity induced by oral azole drugs in mice liver and primary hepatocytes. (2nd September 2019) - Park, Se-Myo; Kang, Seung-Jun; Choi, Mi-Sun; Kim, Soojin; Yoon, Seokjoo; Oh, Jung-Hwa
Abstract: Ketoconazole (KTZ) and itraconazole (ITZ) are antifungal agents that have a broad spectrum of activity against fungal pathogens. However, the therapeutic indications of many antifungal drugs, including those of the azole group, are restricted due to possible hepatotoxicity. We performed toxicogenomic analyses using in vivo and in vitro models to investigate the molecular mechanisms underlying the hepatotoxicity of two azole antifungal drugs. C57BL/6 male mice were treated daily with KTZ or ITZ, sacrificed at days 1 or 7, and the serum biochemistry and histopathology results showed that the KTZ-treated mice exhibited hepatotoxicity. Primary hepatocytes from C57BL/6 mice also exposed to KTZ or ITZ, and the cytotoxic effects of KTZ and ITZ were evaluated; KTZ exerted a greater cytotoxic effect than ITZ. The gene expression profiles in the livers of the 7-day-treated group and primary hepatocytes of the 24-h-treated group for both KTZ and ITZ were comparatively analyzed. Differentially expressed genes were selected based on the fold-changes and statistical significance, and the biological functions were analyzed using ingenuity pathways analysis. The results revealed that genes related to cholesterol synthesis were overexpressed in the liver in the KTZ-treated group, whereas expression of those related to acute phase injury was significantly altered in the ITZ-treated group. Causal gene analyses suggested that sterol regulatory element-binding transcription factors are key regulators that activate the transcription of target genes associated with the hepatotoxicity induced by oral KTZ. These findings enhance our understanding of the molecular mechanisms underlying the hepatotoxicity of azole drugs.